Stock Exchange Performance and Economic Growth in Ghana: Is There A Causal Link? - DZIWORNU, Raymond K; AWUNYO-VITOR, Dadson (Asian Journal of Empirical Research, 2013)
This study empirically examined the causal link between stock exchange performance and economic growth in Ghana, using annual time series data over the period 1990-2012. Secondary data on the performance of the stock exchange: GSE-All Shares/composite Index was obtained from the Ghana stock exchange fact book, whiles that of economic growth was obtained from the Bank of Ghana Quarterly digest. The Granger causality test was employed to determine the causal link between GSE-All-shares/composite index and economic growth in Ghana. The study revealed that GSE-All shares/composite index grew by an average of 20.3 percent over the period. The result of Granger causality test shows that at 5 and 10 percent level of significance, there is a unidirectional causality between the Ghana stock exchange performance indicator and economic growth in Ghana. This suggests that changes in stock market performance precede that of economic growth. Therefore, in order to ensure rapid economic growth, policies which would ensure steady and sustainable growth in GSE-All shares/composite index should be encouraged.